Writing SMARTER goals for professional learning and improving classroom practices. Issue 5 (2nd September 2016) - Brown, Gail; Leonard, Carl; Arthur-Kelly, Michael
Abstract: Writing SMART Goals has recently become an integral part of the landscape of teacher professional learning in Australian schools, including both teacher professional development and performance management in classroom practices. This paper discusses the origins of SMART Goals and the diverse terms and definitions associated with such goal setting. Anecdotal evidence suggests that for some teachers, writing personal, professional or teaching and learning goals may be a daunting task. For school leadership teams, these goals often are the basis for operationalising school improvement over time. We make a case for clarity with SMART Goals within the context of each school, as interpreted and supported by school principals and leadership teams working with their staff. This paper concludes with some tentative suggestions for school leaders intended to improve SMART Goals, and teacher professional learning, over time. We hope this clarification and our suggestions support writing more effective learning goals for both teachers and students over time.